Enhancing Community Capacity through Adaptive English Education and Social Engagement: A Community Service Program in Bukit Sofa Village - Najwa Ramadhani Tarigan; Maslathif Dwi Purnomo; Dwi Yulianti; Jihan Luthfi; Ibtisamah Nasywa; Indah Alya Isnani; Andien Afrizah; Dirza Rizki Purnama; Nazwa Kaila Zira; Nurul Anisya Ray; Qoeddri Farhansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Community Service Program (PEMA), held from July 13 to 21, 2025, in Bukit Sofa Village, Pematangsiantar, represents the implementation of the Tri Dharma of Higher Education, particularly in the area of community engagement. Ten students from the English Education Department actively participated in a series of educational and social programs including teaching English and religious studies at MTs and MDTA Al-Khairiyah and assisting in Posyandu (Integrated Health Services Post) operations. This service not only contributed to the local community but also enhanced students’ leadership, communication, and empathy. This article elaborates on the program’s objectives, scope, methodology, outcomes, and challenges, with the hope of providing a reflective and informative example for similar initiatives.